Synthesis and characterisation of dopedtitanium dioxide structures via aqueous chemical route deposition technique / Mohd Rasydan Mustapha - Mustapha, Mohd Rasydan (2024)
Titanium dioxide (TiO2) became known as one of the most extraordinary nanoparticles in recent years, attracting the attention of researchers from all over the world. The introduction of dopants is a commonly employed technique for surface modification of TiO2, with the aim of enhancing specific aspects of the material, including its structural and optical characteristics. The inherently low photocatalytic properties of TiO2 can be effectively addressed by introducing dopants. Given the close ionic radii of Fe and Ni to TiO2, these transition metals are suitable for substitutional doping, seamlessly replacing titanium atoms in the TiO2 lattice without causing lattice distortions. Doping TiO2 with GO results in synergistic effects, enhances photocatalytic activity. Fe/Ni/Graphene doped TiO2 were prepared by an aqueous chemical route via deposition technique. The resulting samples were characterized by X-ray diffraction (XRD), FESEM and UV–vis. The results demonstrate that the incorporation of Fe as a dopant leads to an increase in the surface area of the structure, accompanied by the formation of flower-like structure. Therefore, the Fe-TiO2 samples display enhanced light absorption characteristics, attributed to a reduction in the band gap.Ni doping is substantiated by a conspicuous reduction in the band gap when compared to pristine samples. 1 at. % showed to obtain the lowest energy band gap. The incorporation of Ni not only induces the formation of denser flower-like structures but also orchestrates a captivating red shift in the absorbance graph, affirming a notable decrease in the band gap value for the doped samples. GO-TiO2 structures with varied GO dopant concentrations, revealing the emergence of a distinctive seaurchin-like morphology, with promoting efficient charge transport within the structures. Notably, the incorporation of 0.001g of GO dopant produces the most consistent morphology, exhibiting the lowest total tensile strain and the highest relative peak intensity orientation. GO-TiO2 samples exhibit low transmission characteristics, indicating their opaque nature.